2011
DOI: 10.4236/ojped.2011.11002
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Low-grade Inflammation and Haematological, Circulatory, Metabolic, and Hepatic Abnormalities in Childhood Obesity

Abstract: Background: Little is known as to the associations between childhood obesity and chronic low-grade inflammation, circulatory, hepatic, metabolic and haematological abnormalities. Methods and Results: A total of 1,871 boys and 1,810 girls were measured anthropometric data, white blood cell (WBCC), platelet count, blood pressure, plasma concentrations of aspartate aminotransferase (AST), alanine aminotransferase (ALT), triglyceride (TG), and highdensity (HDL) lipoprotein cholesterol,. The subjects were classifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…It has been reported that the chronic inflammation state obesity can be caused by oxidative stress generated from the lipid metabolism process when excessive energy intake occures. 30) On hematological analysis, WBCs, including neutrophils and lymphocytes, indicators of inflammation, significantly increased in the C group as compared to the E groups. As no other signs of an inflammation-causing condition were observed, the increases in WBCs might have been linked to the chronic inflammation state obesity of the mice.…”
Section: Discussionmentioning
confidence: 93%
“…It has been reported that the chronic inflammation state obesity can be caused by oxidative stress generated from the lipid metabolism process when excessive energy intake occures. 30) On hematological analysis, WBCs, including neutrophils and lymphocytes, indicators of inflammation, significantly increased in the C group as compared to the E groups. As no other signs of an inflammation-causing condition were observed, the increases in WBCs might have been linked to the chronic inflammation state obesity of the mice.…”
Section: Discussionmentioning
confidence: 93%